2010
DOI: 10.1080/08854720903519976
|View full text |Cite
|
Sign up to set email alerts
|

Pastoral Interventions and the Influence of Self-Reporting: A Preliminary Analysis

Abstract: This article presents the results of 30,700 inpatient visits by chaplains in a healthcare setting over a two-year period. The authors examine the self-report data of chaplains about patients' needs, chaplains' pastoral interventions, and patient outcomes. The article questions the common practice of self-reporting by chaplains and discusses the implication that such self-reporting is more descriptive of chaplains themselves rather than describing the needs of hospitalized patients. Recommendations are made for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…However, there are only a limited number of institutions where these practices are in place (Lublewski-Zienau, Kittel, & Karoff, 2005). In line with the literature, it is clear that the participants were involved in crisis intervention, emotional support, re-questioning of life, helping to find meaning in life, advocating for patient rights, supporting at the time of a loss, promoting religious development, and directing to spiritual resources (Flannelly, Galek, Handzo, Weaver, & Overvold, 2006; Handzo et al., 2008; Lubleswki-Zienau, Kittel, & Karoff, 2005; Montonye & Calderone, 2010; Piderman et al, 2008).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, there are only a limited number of institutions where these practices are in place (Lublewski-Zienau, Kittel, & Karoff, 2005). In line with the literature, it is clear that the participants were involved in crisis intervention, emotional support, re-questioning of life, helping to find meaning in life, advocating for patient rights, supporting at the time of a loss, promoting religious development, and directing to spiritual resources (Flannelly, Galek, Handzo, Weaver, & Overvold, 2006; Handzo et al., 2008; Lubleswki-Zienau, Kittel, & Karoff, 2005; Montonye & Calderone, 2010; Piderman et al, 2008).…”
Section: Discussionmentioning
confidence: 76%
“…A number of researches have highlighted the positive effects of the spiritual support services on patients (Handzo et al., 2008; Montonye & Calderone, 2010; Sharp, 1991; VandeCreek & Lyon, 1997; Özkan & Horozcu, 2016). It is notable that SSSs do not only help patients understand their diseases but they also help healthcare professionals understand their patients (De Vries, Berlinger, & Cadge, 2008; VandeCreek & Burton, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…They are multifaith in theory and practice, and there is a respect for that which is authentically possible when being with and praying with persons of faith traditions that are, or are not, the chaplain's faith tradition (Silton, Asekoff, Taylor, & Silton, 2010;Taylor, 2005;Zucker, Bradley, & Taylor, 2007). Montonye and Calderone (2010) examined chaplain reports of their activities in a 600-bed acute care hospital in Massachusetts. The chaplains included board certified interfaith chaplains, chaplaincy students, and Roman Catholic priests.…”
Section: Chaplains' Activities: Care Of Patientsmentioning
confidence: 98%
“…VandeCreek and Lucas (2001) proposed a system that includes assessment content, interventions, and outcomes, but there is little research on the relationship among these components of care (Montonye & Calderone, 2010). In reality, the content of an assessment protocol for any given chaplain is likely to be idiosyncratic.…”
Section: Chaplains' Activities: Care Of Patientsmentioning
confidence: 98%
“…There is, however, a challenge with chaplains reporting patient feedback themselves. Montonye and Calderone (2010) found that having chaplains record the feedback of hospitalized patients meant that the reporting was more descriptive of the chaplains themselves rather than providing information from the patient perspective. The data that is self-reported by chaplains may be subject to self-reporting bias and there may be a tendency for chaplains to over report perceived positive experiences.…”
Section: Literature Reviewmentioning
confidence: 99%